REPRESENTATIVIDADE FEMININA NAS UNIVERSIDADES PÚBLICAS PARANAENSES: O OLHAR DAS MULHERES GESTORAS - PAULA, JESSICA CRISTIANE ANDRADE DE (2023)
The state universities of Paraná are composed of seven educational institutions. Currently, these universities have five men and two women serving in the highest positions of university administration as their rectors. With this information, it is evident that there is no gender parity in the roster of university rectors, and when examining the histories of these institutions, an even greater disparity from equality becomes apparent. It is also noteworthy that out of the seven institutions, two have never had a woman as a rector. Given this issue, there arises a need for research to identify how female representation in public universities in Paraná occurs, from the perspective of female rectors. The research aims to identify the obstacles faced by women in reaching these positions, as well as to determine the presence of gender discrimination and whether the "glass ceiling" barrier exists in these institutions. To achieve this, this study utilized bibliographic research within the institutions to obtain quantitative data related to the number of employees, educational level, position held, and gender. After data collection, semi-structured interviews were conducted with two current female rectors from different institutions and one former rector who currently presides over APIESP (Association of State Universities of Paraná). The content analysis method used was based on the technique proposed by Bardin (2011), starting with pre-analysis through readings, document selection, and objective formulation. Subsequently, the material was explored, categorized for analysis, and finally, the interpretation of the obtained results was carried out. Text analysis methods were also employed using the IRAMUTEQ software to evaluate the frequency and connections between the terms used during the interviews. Consequently, it was possible to identify that the life stories of each of the interviewees are quite similar, with a foundation in education and the support of their family networks. Gender discrimination within the institutions is also observed, as reported by the female rectors in various environments they frequented. The presence of the glass ceiling barrier is evident, preventing women from reaching top management positions. Therefore, it is proposed that universities create more spaces for dialogue and discussions to promote the social construction of female representation, in addition to implementing legal methods to ensure female representation in leadership positions, thereby breaking down this barrier with fewer difficulties.